2017
DOI: 10.1007/s11600-017-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of seismic doublets occurred on Rudna mine, Poland

Abstract: Seismic events with similar focal mechanisms and similarity of Green's functions exhibit common waveform shapes recorded on the same seismic station. The similarity of seismograms can also be observed in the case of man-induced seismicity on the continuous excavated area. In this work, we focused on strong and potential mininginduced seismic doublets, our study was using concepts of signal analysis, using an in-mine network with quite low dynamic range. Since in such case records for strong events are usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Repeating events were sought in regional scale in China, where it has been shown that their occurrence cannot be related to tectonic loading, mainly due to their short recurrence intervals (Schaff & Richards 2004, 2011. Human activity, such as mining, is also able to produce strong repeating mining tremors (Rudziński et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Repeating events were sought in regional scale in China, where it has been shown that their occurrence cannot be related to tectonic loading, mainly due to their short recurrence intervals (Schaff & Richards 2004, 2011. Human activity, such as mining, is also able to produce strong repeating mining tremors (Rudziński et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Minerals 2022, 12, 1256 18 of 24 16. The obtained results show that: (1) the amplitude ratio Sm/Pm of natural and mine earthquakes are both greater than 1; (2) the amplitude ratio range of natural earthquakes is larger than that of mine earthquakes; (3) the amplitude ratios of most natural and mine earthquakes centralized between 1 and 2.…”
Section: Amplitude Ratio Comparisonmentioning
confidence: 82%
“…It was found that ML-MC mean mine-induced seismicity (MIS) was smaller for unnatural earthquakes than tectonic seismicity (TS). Rudzinski [16] performed signal analyses with both raw signal cross-correlation (CC) and binary signal cross-correlation (BCC) to identify mineinduced seismicity doublets of earthquakes in the Ruhr basin, Poland, and proved that mine activities were able to produce strong mine earthquakes. In 1995, Zhao et al [17] conducted a case study in the Beijing area based on local network data and discussed differences between natural and mine earthquakes, making him the first researcher in China to carry out comparative analyses on natural and mine earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the methods are based on first amplitude or full waveform inversion. While the former approach is less sensitive to signal clipping, an issue often observed during a strong mining tremor recorded by underground networks with low dynamics (Rudziński et al 2017a), the latter can be used in both the time and frequency domains and is expected to be less sensitive to mismodelling of the velocity structure (Cesca et al 2006;Domingues et al 2013). In this paper, we used the full waveform inversion and solved the source mechanism in both domains using the Kiwi tools inversion platform (http://kinhe rd.org; Heimann 2011) and procedures described by Cesca et al (2006).…”
Section: Seismic Data Analysis and Collapse Mechanismmentioning
confidence: 99%